Numerical Analysis of the Three-Dimensional Nonstationary Flow of Ideal Gas in the Last Stage of Turbine Machine Taking into Consideration the Nonaxisymmetric Exhaust Pipe Branch - Gnesin, Vitaly Isaevich; Kolodyazhnaya, Lyubov Vladimirovna; Rzadkowski, Romuald (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
A problem related to the forecast of the aeroelastic behavior and aeroelastic instability of blades (in particular self-oscillations, flutter, and resonance vibrations) becomes of great importance for the development of high-loaded compressor and vent rows and the last turbine stages whose long and flexible blades can be exposed to such phenomena. The solution of this problem requires the development of new models for the nonstationary three-dimensional flow, the use of contemporary numeric methods and the comparison of theoretical and experimental data. This scientific paper gives the data of numerical simulation of the 3-D flow of ideal gas passing through the last stage of turbine machine taking into account the flow nonuniformity caused by guide blades and nonuniform pressure distribution in the exhaust pipe branch and also nonstationary effects caused by blade vibrations. The numerical method is based on the solution of combined aeroelastic problem for the 3-D flow of ideal gas passing through the turbine stage and the nonaxisymmetric exhaust pipe branch including the annular diffuser. To solve the combined problem a partially integral method was used that includes integral equations of gas dynamics (Euler equations) and vibrating blade dynamics (modular approach) at each time step with the information exchange. The given method of the solution of combined aeroelastic problem allows us to predict the amplitude-frequency spectrum of blade vibrations in the three-dimensional flow of ideal gas including forced self-excited vibrations and self-vibrations to increase efficiency and reliability of the blade units of turbine machines.